Ultrassom como pré-tratamento na obtenção do óleo essencial de Melaleuca alternifolia (Maiden e Betche) Cheel. - Vaz, Adriel Rodrigues (2025)
The essential oil market has shown continuous growth in recent years, with a significant increase after the COVID-19 pandemic. In 2022, the global market reached USD 8.8 billion, with projections to reach USD 15.3 billion by 2027, driven by greater awareness of preventive health and a growing preference for natural alternatives. Among plants with potential for essential oil extraction, Melaleuca alternifolia (Tea Tree) stands out for its wide range of applications. However, in Brazil, research has focused primarily on the pharmacological properties of the species, with gaps in studies on the optimization of its cultivation and extraction. This study evaluated the application of ultrasound pretreatment as a strategy to enhance the yield of essential oil extraction from M. alternifolia, aligned with the sustainable principles of Green Chemistry. The effects of three operational parameters during the pretreatment were investigated: sonication time (0, 10, 20, 30, and 40 minutes), ultrasonic bath temperature (25 °C, 40 °C, and 60 °C), and liquid-to-solid ratio (LSR) (10, 15, and 20 mL g⁻¹). The extractions following the pretreatment were performed by hydrodistillation using a Clevenger apparatus. Parameter optimization was conducted using Linear Mixed Models (LMM). The chemical composition of the extracted oils was evaluated using Fourier Transform Infrared (FTIR) spectroscopy and compared to a commercial sample to identify potential structural alterations due to the ultrasound pretreatment. The results demonstrated that increasing the ultrasonic bath temperature during the pretreatment reduced the extraction yield, while prolonging sonication time increased the yield, though in a nonlinear fashion. For the LSR, moderate proportions ensuring full immersion of the material, such as 15 mL g⁻¹, showed the best performance. Spectroscopic analysis indicated that the ultrasound pretreatment did not cause significant changes in the chemical composition of the essential oil. It is concluded that the use of ultrasound as a pretreatment is an efficient approach to optimize the extraction of essential oil from M. alternifolia, enabling an increase of up to 48% in yield compared to conventional hydrodistillation without ultrasound pretreatment.